Regional cooperation and growth triangles in ASEAN (Times Academic Press, 1993)
It is difficult for any one country to provide all the investment incentives to attract global companies. A ready supply of cheap labour, an excellent infrastructure and an abundant source of raw materials, for example, are not always available in the same place. If countries cooperate to exploit their comparative advantages, however, there is not reason why together they cannot offer global companies the requirements they seek. To encourage precisely this kind of cooperation, the Growth Triangle concept was first proposed by Singapore in 1989. How far this concept has come since then is the focus of this book. Comprising papers presented at an international symposium on the Growth Triangle, it analyses (a) the development of the Southern Growth Triangle which consists of Singapore, Johor in Malaysia and the Riau Islands in Indonesia; (b) the potential of the Northern Growth Triangle; and (c) external views of the Growth Triangle. The economic and political implications to establish similar inter-state arrangements in Southeast Asia are also evaluated.